Domínio afetivo: uma discussão teórica de suas dimensões - Martins, Adriano de Morais (2018)
The purpose of this thesis is to bring the debate about the affective domain in Mathematics Education to the national scene and as specific objectives: to understand the affective domain, to select and present a synthesis of texts related to the theme and to identify the theoretical references used. For that, we developed a theoretical study of a qualitative nature, built from the study of international researches that deal with the affective domain and its dimensions, supported by content analysis. The study is justified by the lack of debate in Mathematics Education of this topic in the national scope and the absence of theoretical and theoretical-methodological studies. Throughout our study, we define the affective domain as a set of dimensions formed by beliefs, attitudes, values and emotions. Initially, we sought to understand the historical process that led to the studies that were focused on the beliefs for the studies focused and other dimensions of the affective domain. The construction of the research was based on contemporary studies by international authors, all of 2015. Thus, the studies selected for our research were: the study entitled "Toward a participatory approach to" beliefs "in Mathematics Education" by Jeppe Skott, which dealt with a contemporary vision for the study of beliefs; the study "From Love, Frustration and Mathematics: A Historical-Cultural Approach to Emotions in Teaching and Learning Mathematics" by Luis Radford, who studied the construction of emotions and how they fit into teaching mathematics in a classroom; "The Attitude Construct in Mathematical Education" written by Pietro Di Martino and Rosetta Zan, which dealt with issues related to attitude building; the study by Katrin Rolka and Bettina Roesken-Winter entitled "Network between theories to understand beliefs and their fundamental role in Mathematical Education", which proposed studies from the intercession of different theories about beliefs; and the study written by George N. Philippou and Marilena Pantziara, "Developments of Effective Beliefs in Mathematics Teachers," who advocated studies on effective teacher beliefs that correspond to beliefs about the teacher's ability to organize and execute directed actions to accomplish a task specific. The studies show that when looking at teacher training and student achievement through theoretical lenses aimed at the affective domain, we can obtain better results in the research that addresses teacher training, better understand the difficulties of the students and propose continuing education course more effective. In this way we hope that this study will contribute to Brazilian researchers who intend to study this subject